2008
DOI: 10.1615/jenvironpatholtoxicoloncol.v27.i1.70
|View full text |Cite
|
Sign up to set email alerts
|

The First Pilot Study on Characteristics and Practice Patterns of Kuwaiti Breast Cancer Patients

Abstract: Nongenetic breast cancer risk factors have never been evaluated in Kuwait. Accordingly, we aimed at examining these factors as well as the immune profile of the patients. Fifty stage I breast cancer patients and 50 age group-matched normal controls were assessed for the level of their peripheral blood lymphocyte subsets and for risk factors associated with their demographic and reproductive characteristics and with diet. The percentages of CD4+ T lymphocytes, CD4+:CD8+ ratio, and CD19+ B lymphocytes were signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Moreover, no stratified analysis by menopausal status was performed due to their small sample size. Several studies have examined the link between the consumption of desserts and breast cancer risk [4,9-13,19,20,22,25,26,45] and found a positive association [4,9-13,19,20]. Among them, only one had stratified their analyses by menopausal status [20] and one had stratified by age [4] which can serve as a proxy for menopausal status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, no stratified analysis by menopausal status was performed due to their small sample size. Several studies have examined the link between the consumption of desserts and breast cancer risk [4,9-13,19,20,22,25,26,45] and found a positive association [4,9-13,19,20]. Among them, only one had stratified their analyses by menopausal status [20] and one had stratified by age [4] which can serve as a proxy for menopausal status.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies [4,9-20], although not all [21-29], have found a positive association between sweet foods/drinks and breast cancer risk among premenopausal women [14,16,20], postmenopausal women [16,20] or both combined [4,9-13,15,17-20]. In all of the studies that found a positive association, the frequencies of consumption of several sweet foods or drinks were summed into one [9,11,12,14-19] or two [4,10,13,20] groups. In contrast, among the studies that showed no association, most of them have examined some sweet foods and drinks separately [21,23-25,27-29].…”
Section: Introductionmentioning
confidence: 99%
“…While the risk for breast cancer has been associated with obesity [9][10][11]29] and higher intakes of sweet foods (a.k.a. the Western Diet) with the increased consumption of high fructose corn syrup [30][31][32][33][34], the extent to which various dietary components increase breast cancer risk is still unclear. The increased consumption of fatty acids and/or sugars, in addition to inducing an obese state, can also alter the metabolic profile of an individual, leading to a pre-diabetic state and potentially altering tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…These human investigations are mainly based on case-control studies with fewer long-prospective and interventional ones and the results are not fully consistent and conclusive. Thus, case-control studies have showed inverse associations between olive oil consumption and the risk of this neoplasm, with decreased risk for the highest consumption of olive oil described in cohorts conducted in Mediterranean countries such as Greece [32], Italy [33], Kuwait [34] and Spain [35,36]. In the multi-center case-control study EURAMIC, oleic acid concentration in fat stores showed an inverse association with breast cancer but only in the Spanish center (odds ratio, 0.40), suggesting the role of other olive oil compounds beyond oleic acid in its potential protective effect [37].…”
Section: Human Data: Epidemiological Studies On the Effects Of Medite...mentioning
confidence: 99%